Mutations in PRDM15 are a novel cause of galloway-mowat syndrome - Mann, Nina; Mzoughi, Slim; Schneider, Ronen; Kuhl, Susanne J.; Schanze, Denny; Klambt, Verena; Lovric, Svjetlana; Mao, Youying; Shi, Shasha; Tan, Weizhen; Kuhl, Michael; Onuchic-Whitford, Ana C.; et al. (Journal of the American Society of Nephrology, 2021)
Background Galloway-Mowat syndrome (GAMOS) is characterized by neurodevelopmental defects and a progressive nephropathy, which typically manifests as steroid-resistant nephrotic syndrome. The prognosis of GAMOS is poor, and the majority of children progress to renal failure. The discovery of monogenic causes of GAMOS has uncovered molecular pathways involved in the pathogenesis of disease. Methods Homozygosity mapping, whole-exome sequencing, and linkage analysis were used to identify mutations in four families with a GAMOS-like phenotype, and high-throughput PCR technology was applied to 91 individuals with GAMOS and 816 individuals with isolated nephrotic syndrome. In vitro and in vivo studies determined the functional significance of the mutations identified. Results Three biallelic variants of the transcriptional regulator PRDM15 were detected in six families with proteinuric kidney disease. Four families with a variant in the protein’s zinc-finger (ZNF) domain have additional GAMOS-like features, including brain anomalies, cardiac defects, and skeletal defects. All variants destabilize the PRDM15 protein, and the ZNF variant additionally interferes with transcriptional activation. Morpholino oligonucleotide-mediated knockdown of Prdm15 in Xenopus embryos disrupted pronephric development. Human wild-type PRDM15 RNA rescued the disruption, but the three PRDM15 variants did not. Finally, CRISPR-mediated knockout of PRDM15 in human podocytes led to dysregulation of several renal developmental genes. Conclusions Variants in PRDM15 can cause either isolated nephrotic syndrome or a GAMOS-type syndrome on an allelic basis. PRDM15 regulates multiple developmental kidney genes, and is likely to play an essential role in renal development in humans.
Created from Fastlane, Scopus look-up